USE OF EYELASH EXTENSION AND ITS EFFECTS ON THE ANTERIOR OCULAR SEGMENT - Elvira Pangestu; Titiek Ernawati; Jose L. Anggowarsito (JOURNAL OF WIDYA MEDIKA JUNIOR, 2023)
Background: Eyelash extensions have become the latest cosmetic trend worldwide. Women withlong eyelashes are considered a sign of beauty in various cultures, as a result many women try to improve their appearance by using eyelash extensions. The use of eyelash extensions can interfere with the normal growth and release of eyelashes. It can also cause infection or allergies to the chemicals contained in the glue. The use of eyelash extensions itself also causes many symptoms or complaints that appear in the wearer. Some of the diseases that can be caused are conjunctivitis, blepharitis, and keratitis. Objective: to identify and analyze the use of eyelash extensions and their effects on the anterior ocular segment. Methods: this study used observational analytic with cross sectional method. Sampling time lasted approximately 2 months and data analysis using the Spearman Test. Results: From the results of the study followed by 120 respondents (43 respondents using eyelash extensions and 77 respondents not using eyelash extensions) between the effect of using eyelash extensions and the symptoms of anterior ocular segment abnormalities that arise, it is obtained which means significant results (p<0.05) with the same symptoms. The most common is madarosis (lash loss). Conclusion: the use of eyelash extensions can have an effect on the anterior ocular segment.Keywords: eyelash extension, female student, anterior ocular segment.